2021
DOI: 10.1302/2058-5241.6.200150
|View full text |Cite
|
Sign up to set email alerts
|

Higher rates of surgical and medical complications and mortality following TKA in patients aged ≥ 80 years: a systematic review of comparative studies

Abstract: The purpose of this systematic review was to synthesize studies published since the last systematic review in 2015 that compare outcomes of primary total knee arthroplasty (TKA) in older patients (≥ 80 years) and in younger patients (< 80 years), in terms of complication rates and mortality. An electronic literature search was conducted using PubMed, Embase®, and Cochrane Register. Studies were included if they compared outcomes of primary TKA for osteoarthritis in patients aged 80 years and over to patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Previous studies focused on the analysis of postoperative efficacy and perioperative complications in patients of different ages after TKA ( 19 , 20 , 26 ). Regardless of age, the satisfaction rate of knee surgery is more than 85%, and advanced age does not affect the efficacy of TKA ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies focused on the analysis of postoperative efficacy and perioperative complications in patients of different ages after TKA ( 19 , 20 , 26 ). Regardless of age, the satisfaction rate of knee surgery is more than 85%, and advanced age does not affect the efficacy of TKA ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that preoperative lower hemoglobin was an independent risk factor for complications in patients with SBTKA within 30 days after surgery. Interestingly, a recent study found that lower preoperative hemoglobin levels were identified as an independent predictor of blood transfusion in patients after TKA ( 26 ). In this study, severe postoperative anemia was the most common complication, which well explained the influence of preoperative hemoglobin level on postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, due to the small sample size in patients under 80, it is difficult to reach conclusions on certain rare complications such as periprosthetic joint infection. Nonetheless, elderly patients undergoing TKA must be warned of the heightened risks of general medical complications, as several studies have shown an increased rate in the elderly [6, 13]. Rather than using age as a condition for surgery, we support an approach of basing the decision on comorbidities instead.…”
Section: Discussionmentioning
confidence: 91%
“…Of the published series, studies report aggregate data sometimes containing multiple implant designs [13, 16], or do not report the prosthesis used [2], or have relatively short follow‐up [4, 13, 19, 26, 34] or use outdated prostheses and perioperative protocols. In 2021, Courage et al published a systematic review comparing complications after TKA in patients under or over 80 years of age [6]. They reported higher rates of medical and surgical complications, higher early and late mortality, and longer length of hospital stay.…”
Section: Introductionmentioning
confidence: 99%
“…TKR is a common and safe procedure that relieves the symptoms of arthritis and improves the quality of life [ 12 ]. Nevertheless, like any major surgical procedure, TKR is not without complications, with rates reaching up to 20% for older patients [ 21 ]. The most often referenced complications in the literature are cardiovascular, respiratory and thromboembolic episodes [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%